Developmental and inducible accumulation of gene transcripts involved in alkaloid biosynthesis in opium poppy - Facchini, P.J.; Park, S.-U.
Opium poppy (Papaver somniferum)produces a large number of benzylisoquinoline alkaloids, including morphine and sanguinarine, derived from tyrosine via the branch-point intermediate (S)-reticuline. Molecular clones for the three methlytransferases involved in (S)-reticuline biosynthesis, (S)-norcoclaurine-6-O-methyltransferase (6OMT), (S)-3'-hydroxy-N-methylcoclaurine-4'-O-methyltransferase (4'OMT), and (S)-coclaurine N-methyltransferase (CNMT), were isolated from opium poppy and shown to share extensive homology with the corresponding cDNAs from Japanese goldthread (Coptis japonica). These cDNAs were used together with previously isolated clones for tyrosine/dopa decarboxylase (TYDC), (S)-N-methylcoclaurine-3'-hydroxylase (CYP80B1), berberine bridge enzyme, (BBE), (7S)-salutaridinol 7-O-acetyltransferase (SAT), and codeinone reductase (COR), to compare the accumulation of gene transcripts encoding eight alkaloid biosynthetic enzymes in opium poppy. Transcript levels generally increased in developing seedlings and were consistently high in stems and flower buds, but were more variable in roots and leaves of mature plants. The accumulation of each transcript, with the exception of COR, showed a marked induction in response to elicitor treatment or wounding of cultured cells. Specific gene transcript levels often correlated with the accumulation of morphine or sanguinarine, with notable exceptions. Our data suggest some degree of coordination in the developmental and inducible regulation of alkaloid biosynthetic genes in opium poppy.
Keywords: BENZYLISOQUINOLINE ALKALOID; DEVELOPMENTAL GENE EXPRESSION; ELICITOR-INDUCED GENE EXPRESSION; METHYLTRANSFERASE; OPIUM POPPY; PAPAVER SOMNIFERUM; PAPAVERACEAE; WOUND-INDUCED GENE EXPESSION